The Impact of Extent of Telecommuting on Job Satisfaction: Resolving Inconsistent Findings - Golden, Timothy D.; Veiga, John F. (Journal of Management, 2005)
Although popular management wisdom has suggested that telecommuting enhances job satisfaction, research has found both positive and negative relationships. In this study, the authors attempt to resolve these inconsistent findings by hypothesizing a curvilinear, inverted U-shaped relationship between the extent of telecommuting and job satisfaction. Using hierarchical regression analysis on a sample of 321 professional-level employees, their findings suggest a curvilinear link between extent of telecommuting and job satisfaction, with satisfaction appearing to plateau at more extensive levels of telecommuting. In addition, task interdependence and job discretion moderated this link, suggesting that some job attributes play an important, contingent role.